Impact of the glutamatergic neurotransmission within the A5 region on the cardiorespiratory response evoked from the midbrain dlPAG - González-García, Marta; Carrillo-Franco, Laura; Peinado-Aragonés, Carlos Antonio; Díaz-Casares, Amelia; Gago-Calderón, Belén; López-González, Manuel Víctor; Dawid-Milner, Marc Stefan (Springer Nature, 2022)
Stimulation of the dorsolateral periaqueductal grey matter (dlPAG) in rats evokes an active defensive behaviour together with a cardiorespiratory response characterised by tachypnoea, tachycardia and hypertension. The dlPAG neurons involved in these responses are excitatory, presumably glutamatergic, due to the presence of vesicular glutamate transporter VGLUT2 within their axon terminals. Previously, our group described a functional interaction between dlPAG and the pontine A5 region. Accordingly, in the present work, in order to characterize the role of glutamate within this interaction, experiments were carried out in spontaneously breathing anaesthetized rats (sodium pentobarbitone 60 mg/kg i.p., suplemented with 20 mg/kg i.p.). The cardiorespiratory response evoked by electrical stimulation of the dlPAG (1 ms pulses, 20–50 μA, given at 100 Hz, during 5 s) was analysed before and after the microinjection, within the A5 region, of either kynurenic acid (non-specific glutamate receptor antagonist; 5–10 nmol), DAP-5 (NMDA antagonist; 1 pmol), CNQX (non-NMDA antagonist; 1 pmol) or MCPG (metabotropic antagonist; 0,1 nmol). Kynurenic acid decreased the intensity of both the tachypnoea (p < 0,001) and tachycardia (p < 0,001) induced by dl-PAG stimulation. Blockade of no-NMDA receptors reduced the increase of respiratory frequency, heart rate and pressor response to dl-PAG stimulation (p < 0,01, p < 0,001, p < 0,05 respectively). Blockade of either NMDA or metabotropic receptors reduced the dlPAG-evoked tachycardia and pressor response (p < 0,01; p < 0,05 respectively). These results suggest a neuromodulatory role for A5 region via glutamate neurotransmission of the dlPAG-evoked cardiorespiratory response, confirming the role of the ventrolateral pons in the neuronal circuits involved in respiratory and heart rate control.
Keywords: Transmisión nerviosa; Sistema cardiovascular; Aparato respiratorio; Pontine A5 region; Dorsolateral periaqueductal grey matter (dlPAG); Central cardiorespiratory control; Glutamate; Rat